MODERN LINGUOCULTUROLOGICAL APPROACHES TO THE STUDY OF PHRASEOLOGICAL UNITS (International Conference on Educational Discoveries and Humanities, 2025)
In recent years, phraseological units have become a focal point in interdisciplinary linguistic studies due to their role in reflecting national worldviews, cultural values, and historical memory. The field of linguoculturology—situated at the intersection of language and culture—offers rich, modern approaches to understanding how idiomatic expressions function not only as language tools but also as cultural texts. This article examines contemporary linguoculturological methodologies in the study of phraseological units, highlighting their role in conceptualizing cultural codes, national identity, and cognitive models of different linguistic communities.